Student's perception on case based learning implementation and foreign lecturer participation in medium classroom - Hanifah, Suci; Febrianti, Yosi; Mohd. Zin, Che Suraya (American Institute of Physics Inc., 2018)
Teacher based-learning is commonly practiced in Indonesian Universities. However, this conventional method is lacking in preparing students with required skills such as a problem solving skill. Equipping students with this skill is one of the aims of higher education provider and is also parallel with the implementation of Asian Economic Community that opens the market to all graduates from Southeast Asian countries to compete globally. Thus, the approach of teaching needs to be redesigned from teacher based-learning to case based-learning which able to prepare students with such a skill. This study evaluated the perception of year four pharmacy students from University Islam Indonesia on case based-learning. A total of 233 students included in the study and they were divided into two groups. The first group of students (119 students) were taught by a foreign lecturer while the second group by an internal lecturer. All students received same patient case studies which were obtained from Indonesian and Malaysian hospitals. Students were given a standard form with step by step guides for them to solve the case study. The guides included identification and assessment of drug related problems (DRP) as well as recommendation and monitoring of the DRP. The lecturer was a facilitator who led a discussion and provided feedback on the case study. The perception on the implementation of case based learning was assessed using the perception questionnaire which were distributed to all students at the end of semester. The results showed that majority of students agreed on the implementation of case based learning. A foreign lecturer has a good impact on motivating students to improve their English language.